Patients' perception about risks and benefits of antithrombotic treatment for the prevention of venous thromboembolism (VTE) after orthopedic surgery: a qualitative study. Issue 1 (December 2015) - Najafzadeh, M.; Kim, S.; Patterson, C.; Schneeweiss, S.; Katz, J.; Brick, G.W.; Ready, J.; Polinski, J.M.; Patorno, E.
Abstract Background The 9th edition of the American College of Chest Physicians' Antithrombotic Therapy and Prevention of Thrombosis guidelines emphasize the importance of considering the risk–benefit ratio of "patient-important" outcomes. However, little is known about patients' perception and understanding regarding the different outcomes of antithrombotic treatment after orthopedic surgery, and the factors that influence their decision to use these treatments. Using a series of semi-structured interviews, we explored patients' understanding and perception concerning the benefits and risks of antithrombotic treatment for the prevention of venous thromboembolism (VTE) after joint replacement surgery. Methods A series of semi-structured interviews were conducted with patients who had undergone knee or hip replacement surgery at a tertiary care hospital (Brigham and Women's Hospital, Boston, MA) in 2014. Discussions were recorded and transcribed. Two investigators independently coded and analyzed the data to identify important themes and concepts using the constant comparative method. Results Of 64 patients who were invited, 12 patients (19 %) completed the interviews. The majority of patients (92 %) were aware of the benefits of antithrombotic therapy for reducing the risk of blood clots, while less than half of them had a clear understanding of deep vein thrombosis and pulmonary embolism. While all patients were aware of risk of minor bleeding, only 6 patients (50 %) considered the risk of major bleeding as a possible side effect of antithrombotic treatment. Overall, patients perceived bleeding as a less important outcome than a thrombotic event. The lack of awareness about the risk of major bleeding, the assumption that a short-term exposure would not meaningfully affect bleeding risk, and the assumption that bleeding is a controllable event influenced their perception. Most patients (83 %) stated that their decision to use antithrombotic medications was mainly based on the trust in their physician's expertise. Conclusions Patients perceived thrombotic events as more important outcomes than bleeding events. Patients' understanding of thrombotic and bleeding events varies and may play a key role in their preferences. The majority of patients stated that trust in their physician's expertise had a large influence on their decision to use antithrombotic medications.